Development of Story-Based Emotional Picture Puzzle Media to Improve Early Childhood Emotional Expression Skills - Mukarramah Mukarramah; Rusmayadi Rusmayadi; Herlina Herlina; Herman Herman; Azizah Amal (Universitas Islam negeri Mahmud Yunus Batusangkar, 2026)
This study aims to: 1) identify the needs of children and teachers regarding story-based emotion picture puzzle media to train early childhood emotional expression skills, 2) develop the design of story-based emotion picture puzzle media to train early childhood emotional expression skills, and 3) determine the validity, practicality, and effectiveness of the story-based emotion picture puzzle media in improving early childhood emotional expression skills. This research is a development study using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data collection techniques in this study include observation, interviews, documentation, validation sheets, teacher response questionnaires, and instruments for assessing children’s emotional expression skills. The subjects of this study were early childhood children and teachers at TK Aisyiyah Pammase. The data were analyzed using descriptive qualitative and quantitative analysis techniques. The results of the study show that: 1) the story-based emotion picture puzzle media is highly needed because children still have difficulty recognizing, understanding, and expressing emotions appropriately, while teachers need attractive, concrete, and easy-to-use learning media; 2) the media design was developed in the form of emotion picture puzzles accompanied by simple stories and a teacher’s guidebook; 3) the level of validity of the media obtained an average score of 86.38% with a very valid category, the level of practicality based on teacher responses obtained 99.11% with a very practical category, and the effectiveness of the media showed an increase in children’s emotional expression skills after using the media. Therefore, the story-based emotion picture puzzle media is declared valid, practical, and effective for training early childhood emotional expression skills.